Do National and International Ethics Documents Accord With the Consent Substitute Model for Emergency Research?. (15th December 2020) - Langlois, Adèle; Armstrong, Stephanie; Siriwardena, Aloysius Niroshan
Abstract: In 2010 Largent, Wendler, and Emanuel proposed the "consent substitute model" for emergency research with incapacitated participants. The model provides a means to enroll participants in emergency research without consent, if five conditions are met: 1) the research addresses the patients' urgent medical needs, 2) the risk–benefit ratio is favorable, 3) there are no known conflicts with patients' values or interests, 4) cumulative net risk is minimal, and 5) consent is given as soon as possible. We review national and international ethics laws, regulations, and guidelines to determine 1) whether they accord with the consent substitute model's five conditions and 2) the level of congruence across these documents. We find that only one document meets all five conditions and that there is significant disparity among the documents, particularly between national and international ones. These differences may have stymied international collaboration in emergency research. We recommend that the two international documents used most, the International Council for Harmonization's Guideline for Good Clinical Practice and the World Medical Association's Declaration of Helsinki, are revised to include more specific provisions on emergency medical research.